Intervensi Psikoedukasi Sebagai Strategi Peningkatan Motivasi Kerja pada Pegawai Sekretariat DPRD Kota Makassar - Rezky Fausiah Nur; Andi Nayla Khusnul Khatimah; Nurul Resky Pratiwi; Muh Daud (Universitas Negeri Makassar, 2024)
The Makassar City Regional People's Representative Council Secretariat is a government agency whose function is to assist the Regent/Deputy Regent in efforts to implement regional development in Makassar City, so that community welfare can be realized. In their duties to assist the Regent/Deputy Regent of Makassar City, employees at the Makassar City Regional People's Representative Council Secretariat need a driving force so that all employees collaborate and work sincerely and passionately to achieve regional development planning targets. Work motivation is the most vital driving force in achieving performance. After a need assessment was carried out, the results shown were that approximately 50% of working employees needed increased motivation. Therefore, seeing the problems that existed in the field, the implementation team decided to carry out interventions that were relevant to the existing problems, namely psychoeducational interventions in the form of posters with variables regarding work motivation which aimed to provide staff at the Makassar City DPRD with new insights and knowledge about what what is meant by work motivation, the benefits of work motivation, factors that can cause work motivation to decrease, and how to increase work motivation. The results show that providing psychoeducation has a positive and significant effect on employee work motivation at the Makassar City DPRD Secretariat. So, it can be concluded that providing psychoeducation has a direct impact on employee work processes. Providing psychoeducation can be one of the interventions presented to help employees maintain and increase work motivation.